2015
DOI: 10.2298/vsp130904007p
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of depression and anxiety in patients with chronic liver disease

Abstract: Age and the mean corpuscular volume have significant influence on the HDRS score while unemployment, gastrointestinal bleeding, serum potassium and serum sodium have predictive value for HARS score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 45 publications
4
20
0
Order By: Relevance
“…A total of 39 studies assessing symptom prevalence were included (see Supplementary Material). 2058 The majority reported data from North America (16) and Europe (14), although Asia (8) and Africa (1) were also covered. Most were cross-sectional studies conducted while patients were outpatients or stable after hospitalization.…”
Section: Symptom Prevalence Of Patients With End-stage Liver Diseasementioning
confidence: 99%
“…A total of 39 studies assessing symptom prevalence were included (see Supplementary Material). 2058 The majority reported data from North America (16) and Europe (14), although Asia (8) and Africa (1) were also covered. Most were cross-sectional studies conducted while patients were outpatients or stable after hospitalization.…”
Section: Symptom Prevalence Of Patients With End-stage Liver Diseasementioning
confidence: 99%
“…The sampling method and detailed methodology were published previously 30,32 . We performed a cross-sectional study for a period of one year (October 2009 -October 2010).…”
Section: Patientsmentioning
confidence: 99%
“…The study was conducted at the Clinic for Gastroenterology and Hepatology, Clinical Center of Serbia, Belgrade, and included 103 patients with chronic liver disease (chronic hepatitis or cirrhosis). Exclusion criteria were: age < 18 years, psychiatric disorders, acute complications of the CLD, hepatic encephalopathy (grade > 2) and liver transplantation 30,32 .…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ismail et al (2007) used standard psychiatric interview (Schedules of Clinical Assessment in Neuropsychiatry) to diagnose MDD in patients with diabetes and their first foot ulcer. In a cross-sectional study, Popović et al (2015) used the Hamilton depression rating scale (HDRS) in patients with CLD and found that depression was present in 62.9% of them. In addition, a number of studies on CLD have instead used self-report questionnaires (Bellentani et al, 1994; Dwight et al, 2000; Dan et al, 2006).…”
Section: Introductionmentioning
confidence: 99%